2023
DOI: 10.1002/ncp.11041
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of normal saline and antiseptic solution effect on the early peristomal infection rates of patients with percutaneous endoscopic gastrostomy tubes: A randomized double‐blind study

Abstract: BackgroundThis study's aim was to compare the efficacy of normal saline (NS) with that of antiseptic solution in early peristomal skin care after percutaneous endoscopic gastrostomy placement in terms of peristomal infection incidence.MethodsThis was a randomized controlled double‐blind study conducted at a university hospital between December 2019 and April 2021. All patients who underwent percutaneous endoscopic gastrostomy and met the inclusion and exclusion criteria were included in the study. The study po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…This disparity in research methodologies may be attributed to the distinction between our human study and their ex vivo study. Furthermore, several studies comparing the efficacy of NS and PHMB-B in patients with infected wounds found no significant differences in rates of dehiscence, wound closure, wound recurrence, amputation, or mortality between the two solutions 39 41 . These findings are consistent with the results of our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This disparity in research methodologies may be attributed to the distinction between our human study and their ex vivo study. Furthermore, several studies comparing the efficacy of NS and PHMB-B in patients with infected wounds found no significant differences in rates of dehiscence, wound closure, wound recurrence, amputation, or mortality between the two solutions 39 41 . These findings are consistent with the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with the results of our study. The clinical efficacy, cost-effectiveness, greater accessibility, non-irritating and non-allergenic properties of NS may position it as the preferred choice for expanding the utilization of NPWTi-d in larger patient populations 40 , 41 .…”
Section: Discussionmentioning
confidence: 99%